FGF13 regulates proliferation and differentiation of skeletal muscle by down‐regulating Spry1. (31st July 2015) - Lu, Hongzhao; Shi, Xine; Wu, Guofang; Zhu, Jiayu; Song, Chengchuang; Zhang, Qiangling; Yang, Gongshe
Abstract Objectives Generally, the secretory forms of FGF are known to regulate cell proliferation, differentiation and morphogenesis by binding to the extracellular domain of cell surface receptors. Intracellular FGFs (FGF11‐14) are expressed principally in the nervous system. FGF13 is a microtubule‐stabilizing protein that regulates neuronal polarization and migration. Previous studies have reported high expression of FGF13 in cultures of single muscle fibres. However, functions of FGF13 in muscle development have not been explored. Materials and methods Real‐time RT‐PCR was performed to detect expression of FGF13 during C2C12 muscle cell proliferation and differentiation. To further understand the role of FGF13, its effects on proliferation and differentiation were examined by western blot analyses of cells transfected with FGF13 siRNA or FGF13 expression plasmids, or treated with chemical MEK inhibitors. Effects of FGF13 on related signalling pathways in C2C12 cell proliferation and differentiation were determined. Results FGF13 inhibited C2C12 cell proliferation by up‐regulating p27 mRNA level and by down‐regulating Cyclin E protein expression, during cell proliferation. Additionally, FGF13 down‐regulated Spry1 protein expression, activating the ERK1/2 pathway by phosphorylation and leading to C2C12 cell differentiation inhibition. Consequently, FGF13 seemed to function as a repressor of myoblast differentiation via the ERK1/2 pathway. Although FGF13 inhibited Spry1 regardless of cell proliferation or differentiation, its pathway activation occurred only during the stage of myoblast differentiation. Conclusions FGF13 inhibited C2C12 cell proliferation and differentiation by down‐regulating Spry1. These findings indicate that FGF13 played a negative regulatory role in skeletal muscle development.